The rest of you - Blue, Maame (Amistad, 2024)
An emotionally wrenching novel, set in today's London and 90s Ghana, exploring generational trauma and what it means to be Black British, surviving between the gaps of knowledge around familial migrant journeys. On the cusp of thirty, Ghanaian Londoner Whitney Appiah was born with a special gift. The massage therapist can physically sense where her clients' trauma lies and heal them. But Whitney has no idea that she too is suffering. Tragic events from her youth have left a terrible, unseen mark. When a dangerous encounter with the man she's dating triggers a wave of fragmented recollections, Whitney embarks on a journey to reclaim her memories and the truth that is buried deep in her early years growing up in Kumasi. Spanning three decades, told through the viewpoints of Whitney, her aunts, Gloria and Aretha, and their house help, Maame Serwaa, The Rest of You explores what happens when we try to resolve the mysteries of our past. Perfect for fans of Candace Carty Williams' Queenie, Brit Bennett's The Vanishing Half and Anna Hope's Expectation. 'A novel that doesn't shy away from the modern issues of being Black and female. At times heartbreaking, this portrait of a family coming to terms with a tragic past is vivid and tender' - Louise Hare, author of This Lovely City